2003
DOI: 10.1007/s00592-003-0057-3
|View full text |Cite
|
Sign up to set email alerts
|

Body composition in coeliac disease adolescents on a gluten-free diet: a longitudinal study

Abstract: Our aim was to evaluate body composition in a group of coeliac disease adolescents on a gluten-free diet and to re-examine them at the end of the adolescence spurt. We studied 48 patients (group 1A), 30 age-matched healthy controls (group 2A), 11 group 1A patients after 4 years (group 1B) and 11 adolescents who were age- and sex-matched with group 1B (group 2B). Weight, height, bone mineral content, fat mass, fat-free mass (FFM) and bone mineral density were evaluated using dual-energy X-ray absorptiometry. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 8 publications
2
20
0
1
Order By: Relevance
“…Similarly, Sonti et al 15 demonstrated that men with CD diagnosed in adulthood were shorter than men in the general population. So far, only one small study performed by Carbone et al 20 showed that adolescent patients with CD were shorter than controls irrespective of gender. Overall, some reports showed reduced height only in men,11 15 21–22 whereas others showed reduced height only in women 23.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Sonti et al 15 demonstrated that men with CD diagnosed in adulthood were shorter than men in the general population. So far, only one small study performed by Carbone et al 20 showed that adolescent patients with CD were shorter than controls irrespective of gender. Overall, some reports showed reduced height only in men,11 15 21–22 whereas others showed reduced height only in women 23.…”
Section: Discussionmentioning
confidence: 99%
“…Serum tTG‐Abs detected with a fluid‐phase radioimmunoprecipitation method (RIA) proved to be a sensitive test, not only at diagnosis but also during follow‐up, with the result that this is the most reliable in detecting the non‐adherence to the diet 11, 12 . It is well known that a good compliance to the diet is particularly important in children and in adolescents, permitting at the same time to obtain optimal growth 13, 14 and to avoid complications including autoimmune pathologies 15, 16 . Recently, we demonstrated that RIA tTG‐Abs could be detected in human saliva, a body fluid that can easily be obtained by non‐invasive techniques and bypassing the unpleasant blood sample collection is particularly helpful in children for CD‐screening purposes 17 .…”
Section: Introductionmentioning
confidence: 99%
“…The nutritional profile of a CD patient was described as low weight, short stature, loss of muscle, bone, and fat mass; and other nutritional deficiencies such as loss of vitamins and minerals until the beginning of the 21 st century. 7,8,[20][21][22][23] The recovery of body composition and nutritional status only occurred after following a gluten-free diet. The profile of the individual with CD after beginning a dietary treatment shows an increase in weight and fat mass, and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…The only body parameter without significant difference between the two groups was total body fat mass. Carbone et al 8 in 2003 stressed that children and adolescents recovered weight, BMI, and %GC after four years of gluten-free diet compared with the control group, however, still showed a deficit in height and fat-free mass. In this study, although there is no significant difference in the bodily parameters between the two groups, the control group showed higher average weight, height, BMI, %GC, CA, and MM than the study group, suggesting a discreet tendency to reduction in bodily parameters in CD patients related to gluten-free diet time and adherence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation